The Effect of Niosomal System (Span 60-Cholesterol) on Diclofenac Sodium Preparation Characteristics and Diclofenac Sodium Preparation of Hydroxypropyl Cellulose Gel Base (HPC) - Adeltrudis Adelsa Danimayostu; Esti Hendradi; Tutiek Purwanti (Lembaga Penelitian dan Pengabdian kepada Masyarakat, Universitas Brawijaya, 2017)
Diclofenac sodium is a lipophilic drug. That characteristic makes it difficult to disperse well in hydrophilic gel base. The niosome with its vesicle system could overcome that low dispersibility. It affects penetration by reducing water loss in trans-epidermal layer and change lipid bilayer conformation. The present study was designed to investigate the effect of niosomal system (Span 60–Cholesterol) on preparation characteristics and diclofenac sodium penetration of hydroxypropyl cellulose (HPC) gel base. We examined three different formulas in HPC gel base. Formula III was made in niosomal system. Preparation characteristics were evaluated with organoleptic and acidity tests. Drug penetration was checked using apparatus 5-paddle over disk and 0.45 μm Milipore membrane impregnated with isopropyl myristate. The solution is phosphate buffer saline pH 7.4±0.05 in temperature 37±0.5°C. All of the data were evaluated based on one way ANOVA and continued with HSD test. It was concluded that niosomal system (span 60-cholesterol) has an influence in increasing pH value and penetration (based on flux value and permeability) of diclofenac sodium in HPC gel base.